Rire des mots de l’étranger dans The Real Life of Sebastian Knight et Pnin de Vladimir Nabokov - Julie Loison-Charles (Revue LISA)
In Nabokov’s American novels, the main characters are often foreigners who have a dazzling mastery of the English language. In The Real Life of Sebastian Knight and Pnin however, the non-native speakers speak an English that is more of a strange idiolect, an interlanguage full of mistakes which make them scapegoats for the English-speaking community of readers and narrators. However, their exclusion tends to disappear as their brand of English sheds light on the inner richness of this language. Finally, the discrepancy between two types of complicity – against the foreigner or with him – gives way to a moral redefinition of laughter.